Analisis Semantik Makna Kata Shahib dan Derivasinya dalam Al-Qur’an Juz 29 - Banjarnaor, Riadi; Siregar, Husnatul Hamidiyyah (INCARE, International Journal of Educational Resources, 2025)
This research aims to conduct a semantic analysis of the meaning of the word sh??ib (????) and its derivations in the Qur'an, Juz 29. The background of the study lies in the complexity of meaning (polysemy) in the language of the Qur'an, which necessitates a comprehensive contextual and semantic approach, rather than relying solely on lexical definitions. The word sh??ib, generally meaning "friend" or "owner," appears in Juz 29 in various contexts, particularly those related to eschatological and moral themes, such as a???bu an-n?r (inhabitants of the Fire) and a???bu al-yam?n (the People of the Right Hand). The method employed is qualitative descriptive-analytical, focusing on lexical and grammatical analysis. The data were inventoried using the Quran Arabic Corpus and analyzed with reference to authoritative dictionaries such as Al-Ashfahani’s Al-Mufradat fi Gharibil Qur'an. The findings indicate that the word sh??ib is mentioned 8 times in Juz 29 with 4 forms of derivation (such as a???b and ???ibah). Lexically, the root ?-?-b signifies intense togetherness and loyalty. However, relationally, its meaning expands to include "Permanent Inhabitant" (e.g., in a???bu an-n?r), "Spouse" (???ibah), "Owner" (???ibi al-jannah), and "Entity Intensely Involved" (???ibi al-??t). The conclusion asserts that understanding the word sh??ib in the Qur'an requires grasping its relational meaning based on the syntagmatic and paradigmatic context of the verses, transcending its basic meaning.